2020
DOI: 10.1111/dom.14100
|View full text |Cite
|
Sign up to set email alerts
|

Ultra rapid lispro improves postprandial glucose control compared with lispro in patients with type 1 diabetes: Results from the 26‐week PRONTO‐T1D study

Abstract: Aims To evaluate the efficacy and safety of ultra rapid lispro (URLi) versus lispro in adults with type 1 diabetes in a 26‐week, treat‐to‐target, phase 3 trial. Materials and methods After an 8‐week lead‐in to optimize basal insulin glargine or degludec, patients were randomized to double‐blind mealtime URLi (n = 451) or lispro (n = 442), or open‐label post‐meal URLi (n = 329). The primary endpoint was change from baseline glycated haemoglobin (HbA1c) to 26 weeks (non‐inferiority margin 0.4%), with multiplicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
113
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 71 publications
(133 citation statements)
references
References 21 publications
18
113
1
1
Order By: Relevance
“…PRONTO-T1D demonstrated that mealtime and postmeal URLi are non-inferior to lispro in terms of change in HbA1c following 26 weeks of treatment [21]. In addition, mealtime URLi was superior to lispro at reducing 1-and 2-h PPG excursions during the meal test [21].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…PRONTO-T1D demonstrated that mealtime and postmeal URLi are non-inferior to lispro in terms of change in HbA1c following 26 weeks of treatment [21]. In addition, mealtime URLi was superior to lispro at reducing 1-and 2-h PPG excursions during the meal test [21].…”
Section: Discussionmentioning
confidence: 98%
“…The analyses have already been described for the overall population [21]. These methods were applied to the Japanese population in a pre-specified subset analysis, although statistical power was not taken into consideration, and p values are provided as a reference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations